DISCIPLINARY OFFENSES OF NON-COMMISSIONED POLICE OFFICERS IN PROTECTION AND CROWDS CONTROL DIVISION, METROPOLITAN POLICE DIVISION - Sutthisarn, Thatchapon (Journal of MCU Nakhondhat, 2021)
The objectives of this research article were 1) to study the Disciplinary Offenses of Non-commissioned Police Officers in Protection and Crowds Control Division, Metropolitan Police Division, and 2) to study the Disciplinary Offenses of Non-commissioned Police Officers in Protection and Crowds Control Division, Metropolitan Police Division classified by personal factors and knowledge factors about the National Police Act 2547. The sample used in the research was Non-commissioned Police officers in Protection and Crowds Control Division, Metropolitan Police Division consisted of 153 people, by using the Taro Yamane sampling formula. The instrument used in the study was a questionnaire. The data obtained from the population questionnaires were processed by computer programs. The data analyzed were frequency, percentage, mean, standard deviation, and one-way ANOVA. When differences were found, the mean difference was analyzed by the LSD method. The research results showed that 1) Disciplinary offenses of Non-commissioned Police officers in Protection and Crowds Control Division, Metropolitan Police Division, the overall average was at a low level. The most offense was you receive welfare subsistence allowance for living. 2) Comparison of disciplinary offenses of Non-commissioned Police Officers, who have different of age of service, levels of education, income and knowledge of the National Police Act BE 2547. There are different disciplinary actions with statistical significance at the .05 level. As for Non-commissioned the Police Officers, who had different debt and welfare burdens, there were no different disciplinary offenses